2016
DOI: 10.1111/apt.13779
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to tenofovir disoproxil fumarate plus peginterferon alfa‐2a combination therapy for chronic hepatitis B

Abstract: SUMMARY BackgroundIn patients with chronic hepatitis B, tenofovir disoproxil fumarate (TDF) plus pegylated interferon (PEG-IFN) for 48-weeks results in higher rates of hepatitis B surface antigen (HBsAg) loss than either monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 26 publications
1
31
1
Order By: Relevance
“…Theoretically, a combined NA and PegIFNa approach may provide advantages by combining the potent antiviral effect of NA plus the immune modulation of IFNa. 1,56,62,63 The evidence for superiority of such a combined approach, however, is lacking, and there are still many unresolved issues with respect to patient selection, timing, as well as the duration of the combination strategy, which may be addressed in future studies.…”
Section: 5657mentioning
confidence: 99%
“…Theoretically, a combined NA and PegIFNa approach may provide advantages by combining the potent antiviral effect of NA plus the immune modulation of IFNa. 1,56,62,63 The evidence for superiority of such a combined approach, however, is lacking, and there are still many unresolved issues with respect to patient selection, timing, as well as the duration of the combination strategy, which may be addressed in future studies.…”
Section: 5657mentioning
confidence: 99%
“…Similar trends have been described for individual studies in the literature. For example, a similar genotype effect (larger decline in HBsAg levels for genotype B vs C) has been observed, albeit for HBsAg declines at week 48, in HBeAg‐negative and ‐positive patients 31,32 . In addition, baseline HBsAg levels have been described as predictors for HBsAg loss in HBeAg‐negative patients 33 .…”
Section: Discussionmentioning
confidence: 68%
“…Regarding the efficacy of adding PEG-IFN to NA therapy, Ouzan et al reported that the addition of 180  μ g of PEG-IFN- α -2a for a maximum of 96 weeks based on HBsAg-titer monitoring led to a loss of HBsAg and cessation of NA therapy in six out of ten patients (60%), with no relapse [17]. Marcellin et al reported that the rates of HBs Ag loss were significantly higher in the group treated with tenofovir plus PEG-IFN for 48 weeks than in the group (6.5%) treated with tenofovir plus PEG-IFN for 16 weeks and tenofovir for 32 weeks (0.5%) [18]. Therefore, longer-term add-on PEG-IFN- α -2a therapy would be needed for the cessation of NA.…”
Section: Discussionmentioning
confidence: 99%